Strategi Peningkatan Efektivitas Masyarakat Peduli Api (MPA) Dalam Pengendalian Kebakaran Hutan di Provinsi Bali - DARJO, DARJO; SUARNA, I WAYAN; WIJANA, GEDE (Agrotrop : Journal on Agriculture Science; Vol 11 No 2 (2021), 2021)
Strategy For Improving Effectiveness of Fire Care Society (MPA) in Control of Forest Fire in Bali Province. Land and forest fires seem to be an annual disaster in Indonesia. The Ministry of Environment and Forestry is initiated to form Fire Care Community Groups, called Fire Care Society (MPA). MPA in Bali has been established since 2012. The study is needed to determine the community perception who live around the forest areas, to determine the effectiveness of MPA, and to analyzed strategic increases the effectiveness of MPAregarding forest fires controlling. Research data has been collected through a closed questionnaire to compile the respond of respondents in the google form. The respondent consisted of MPA member and non-member and related stakeholders . The types of data that been collected include respondent’s perceptions, MPA participation, and implementation of Perdirjen PPI number 3, 2018. These data then analyzed with the SWOT method. The results showed that the MPA and non-MPA members have positive perception of natural factor and human behavior as a factor of forest fires. The highest value of MPA’s participation in fires-fighting is 3.71 and participation influenced by environmental factors valued at 3.84. While the implementation of Perdirjen PPI decree is 66.39%. The SWOT analysis shows the MPA in progressive strategic S-O. So this study concludes that the MPA hasn’t been fully effective. The effectiveness can be improved by providing adequate support through clear regulations, budget allocations, and increasing human resource capacity.